Glucose-sensing mechanisms in pancreatic beta-cells. - MacDonald, P; Joseph, J; Rorsman, P (2005)
The appropriate secretion of insulin from pancreatic beta-cells is critically important to the maintenance of energy homeostasis. The beta-cells must sense and respond suitably to postprandial increases of blood glucose, and perturbation of glucose-sensing in these cells can lead to hypoglycaemia or hyperglycaemias and ultimately diabetes. Here, we review beta-cell glucose-sensing with a particular focus on the regulation of cellular excitability and exocytosis. We examine in turn: (i) the generation of metabolic signalling molecules; (ii) the regulation of beta-cell membrane potential; and (iii) insulin granule dynamics and exocytosis. We further discuss the role of well known and putative candidate metabolic signals as regulators of insulin secretion.